PENERAPAN MODEL COOPERATIVE TIPE LEARNING TOGETHER DALAM PEMBELAJARAN MENULIS TEKS LAPORAN HASIL OBSERVASI PADA KELAS X DI SMKN 1 BALONGAN TAHUN PEMBELAJARAN 2022/2023 - Fajri, Khoirul; Apriyanto, Ade; Warliyanto, Warliyanto (JURNAL RISET PENDIDIKAN DAN PENGAJARAN, 2023)
The aim of this research is to determine if the learning together model is effective in teaching class X students of SMK N 1 Balongan how to write observation report texts, and to understand the process involved. The research method used in this study is quantitative. The researcher chose the Quasi Experimental Design as the experimental method. The sampling technique used was Probability Sampling, resulting in X TITL 1 as the experimental class and X TITL 2 as the control class, with a total of 35 students in each class. The data collection techniques included observation and tests. The research instruments used were interviews, tests, observations, lesson plans, and assessment sheets. The data analysis involved pretest and posttest comparisons, as well as observation results analyzed using SPSS 24. Based on the findings described in the previous chapter, it can be concluded that learning to write observation report texts using the learning together model is effective for class X students of SMK N 1 Balongan. The t-value obtained from the Coefficients table is 4.421, while the t-table value with a significance level of 0.001 is 1.668. The comparison between the two values shows that t-value > t-table (4.421 > 1.668), indicating that Ha is accepted and Ho is rejected. This means that there is a positive and significant relationship between the application of the cooperative learning together model in teaching class X students how to write observation report texts at SMK N 1 Balongan.